Self-reported skills and self-confidence in point-of-care ultrasound: a cross-sectional nationwide survey amongst Finnish emergency physicians - Ossi Hannula; Ville Hällberg; Anna Meuronen; Olli Suominen; Suvi Rautiainen; Ari Palomäki; Harri Hyppölä; Ritva Vanninen; Kalle Mattila (BMC Emergency Medicine, 2023)
Abstract Background The use of point-of-care ultrasound (POCUS) is increasing. Numerous investigators have evaluated the learning curves in POCUS, but there are no published studies on how emergency physicians perceive their own competence level with this skill. Methods A nationwide survey amongst Finnish emergency physicians was conducted. The respondents reported their use of POCUS and how it has affected their clinical decision-making. The number of POCUS examinations performed was compared to the self-assessed skill level with different applications. Cut-off values were determined for the number of examinations required to acquire a good self-assessed skill level in each POCUS application. The correlation between self-confidence and the self-estimated skill level was analyzed. Several different statistical methods were used, such as Student’s t-test, Pearson’s correlation test, Loess method and ROC curve analysis. Results A total of 134 out of 253 Finnish emergency medicine specialists and residents (52%) responded to the survey. The most commonly used POCUS applications were POCUS-assisted procedures, pleural effusion and pneumothorax, inferior vena cava and lower extremity deep venous thrombosis. The initial rate of perceived skill acquisition was very steep with the curve flattening with greater skill and more experience. The number of examinations performed to reach a self-assessed good competence varied from seven to 75 with different applications. The lowest cut-off point for self-assessed good competence was obtained for rapid ultrasound for the shock and hypotension-protocol and the highest for focused cardiac examinations. There was an excellent correlation between self-confidence and the self-assessed skill level. Conclusions The Finnish emergency practitioners’ self-assessed development of POCUS skills parallels the previously published learning curves of POCUS. The correlation of self-confidence and the self-assessed skill level was found to be excellent. These findings add information on the development of perceived POCUS skills amongst emergency physicians and could complement a formal performance assessment.